Bovine Holo-Beta-Lactoglobulin Cross-Protects Against Pollen Allergies in an Innate Manner in BALB/c Mice: Potential Model for the Farm Effect - Afify, Sheriene Moussa; Pali-Schöll, Isabella; Hufnagl, Karin; Hofstetter, Gerlinde; El-Bassuoni, Maha Abdel-Rafea; Roth-Walter, Franziska; Jensen-Jarolim, Erika (Frontiers in Immunology, 2021)
The lipocalin protein beta-lactoglobulin (BLG) is a major protein compound in cow´s milk and we detected it in cattle stable dust. BLG may be a novel player in the farm protective effect against atopic sensitization and hayfever. In previous studies we demonstrated that only ligand-filled holo-form of BLG prevented sensitization to itself. Here, we investigated whether holo-BLG could, in an innate manner, also protect against allergic sensitization to unrelated birch pollen allergens using a murine BALB/c model. BALB/c mice were nasally pretreated 4 times in biweekly intervals with holo-BLG containing quercetin-iron complexes as ligands, with empty apo-BLG or sham-treated. Subsequently, mice were intraperitoneally sensitized 2 times with apo-BLG, or unrelated birch pollen allergen apo-Bet v 1 together with aluminum hydroxide, respectively. After subsequent systemic challenge with BLG or Bet v 1, body temperature drop was monitored by anaphylaxis imaging. Specific antibodies in serum and cytokines of BLG- and Bet v 1-stimulated splenocytes were analyzed by ELISA. Additionally, human peripheral blood mononuclear cells of pollen allergic subjects were stimulated with apo- and holo-BLG before assessment by FACS. Prophylactic treatment with the holo-BLG protected against allergic sensitization and clinical reactivity not only to itself, but also to Bet v 1 in an unspecific manner. Pretreatment with holo-BLG resulted in significantly lower BLG– as well as Bet v 1–specific antibodies and impaired antigen-presentation with significantly lower numbers of CD11c+MHCII+ cells expressing CD86. Apo-BLG-stimulated splenocytes of BLG-sensitized mice released significantly less Th2-associated cytokines only when they were pretreated with holo-BLG. Similarly, in vitro stimulation of PBMCs from birch pollen allergic subjects with holo-BLG resulted in a relative decrease of CD3+CD4+ and CD4+CRTh2 cells, but not of CD4+CD25+CD127- Treg cells, compared to apo-BLG stimulation. In conclusion, prophylactic treatment with holo-BLG protected against allergy in an antigen-specific and unspecific manner by decreasing antigen presentation, specific antibody production and abrogating a Th2-response. Holo-BLG therefore promotes immune resilience against pollen allergens in an innate manner and may thereby contribute to the farm protective effect against atopic sensitization.